The Optimization of Chlorophyll Extraction from Ulva Sp. with Ultrasound-Assisted Liquid Biphasic Systems Method - Susilowati; Humaidi, Fakhri Arkaan; Fachri, Boy; Palupi, Bekti; Rizkiana, Meta Fitri; Rahmawati, Istiqomah; Amini, Helda Wika (Universitas Tidar, 2024)
Ulva sp. is a type of green algae that is easily found in the shallow seas of Indonesia and contains various bioactive compounds. Chlorophyll is a bioactive compound that functions as a natural dye, free radical scavenger, and antioxidant in the body. Chlorophyll extraction with conventional methods requires a relatively long time and large amount of solvent. In this research, chlorophyll extraction from Ulva sp. with the Ultrasound-Assisted Liquid Biphasic System (UALBS) method. Ulva sp. as much as 2.5 grams mixed in acetone solvent, added K2HPO4 solution, and carried out the sonification process in a dark room. The extraction process performs at a parameter range of 5-15 minutes, ratio 0.05-0.1 g/mL, and 60-100 mesh particle size. The extracted filtrate was added with petroleum ether and distilled water to form a biphasic condition. The extracted chlorophyll was analyzed with chromatography and spectrophotometry method. Antioxidant activity was analyzed using the DPPH method. The optimum result of Ulva sp. chlorophyll extraction at an extraction time of 10 minutes, the ratio of solids to solvent was 0.1, the particle size of 60 mesh produced a yield of 1.88% with chlorophyll a 20.13664%, chlorophyll b 21.58672% and total chlorophyll 41.71012%, and the percentage inhibition 45.32%.